2012
DOI: 10.1503/cjs.000411
|View full text |Cite
|
Sign up to set email alerts
|

Monopolar electrocautery versus ultrasonic dissection of the gallbladder from the gallbladder bed in laparoscopic cholecystectomy: a randomized controlled trial

Abstract: RESEARCH • RECHERCHEMonopolar electrocautery versus ultrasonic dissection of the gallbladder from the gallbladder bed in laparoscopic cholecystectomy: a randomized controlled trial Background: Ultrasonic dissection has been suggested as an alternative to monopolar electrocautery in laparoscopic cholecystectomy because it generates less tissue damage and may have a lower incidence of gallbladder perforation. We compared the 2 methods to determine the incidence of gallbladder perforation and its intraoperative c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 16 publications
1
26
3
Order By: Relevance
“…Particularly, the same-day discharge rate was similar (87 %) in the study groups. Mean operative time in previous randomized studies comparing ultrasonic dissection method and diathermy dissection seems to be lower in ultrasonic dissection method (27-60 vs 34-65 min) in contrast to our study showing similar operating time in both study groups [7,8,15,16].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Particularly, the same-day discharge rate was similar (87 %) in the study groups. Mean operative time in previous randomized studies comparing ultrasonic dissection method and diathermy dissection seems to be lower in ultrasonic dissection method (27-60 vs 34-65 min) in contrast to our study showing similar operating time in both study groups [7,8,15,16].…”
Section: Discussioncontrasting
confidence: 99%
“…Overall, intraoperative gallbladder perforations occur in 8.6-20 % during conventional diathermy dissection [25,26]. However, in randomized series comparing diathermy and ultrasonic dissection gallbladder perforations (40-51 vs 16-26 %) seems to occur less often with ultrasonic dissection [7, 15,16]. In our study, intraoperative perforations occurred more often in the ultrasonic group (27 vs. 20 %), although the difference was not statistically significant.…”
Section: Discussioncontrasting
confidence: 55%
“…In various studies done previously, there is a significant difference in the operating time between the harmonic and electrocautery groups. This can be explained by the fact that the harmonic scalpel is a multifunctional instrument [ 1 - 2 , 7 ]. It replaces four instruments routinely used in conventional LC, namely, the dissector, clip applier, scissors, and electrosurgical hook/spatula.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the clinical and surgical advantage of the Harmonic scalpel over conventional techniques in different surgical areas, including thyroidectomy [ 10 13 ], cholecystectomy [ 14 , 15 ], and colectomy [ 16 19 ]. Furthermore, this device has been widely used in both laparoscopic and open surgeries [ 10 ].…”
Section: Introductionmentioning
confidence: 99%